Selected Profile and Factors Affecting the Academic Performance in Social Studies of Grade 10 Students: Input for an Intervention Program - Nicolas, Rowena E. (Future Science / FSH-PH Publications, 2022)
Education is deemed to be an important tool for social mobility. Because of this, quality education is one of the many goals of Filipinos who wanted to have an improvement in their lives. However, one major issue in Philippine education is the poor academic performance of the students. Thus, this paper focuses on the profile of selected Grade 10 students of Bagong Silangan High School and its impact on their academic performance in Social Studies. The study utilized a descriptive research design. Pearson correlational statistical analysis was done to determine the relationship among variables. Results showed that most of the student respondents’ parents were high school graduates (43.81%), do not have occupation (57.78%), have family monthly income ranging from 10,000-19,999 (43.17%) and have 3 siblings (25.40%). Results also revealed that the extent of the factors affecting the academic performance of students in Social Studies in terms of teachers’ competency, learning environment, parents’ aspiration, student-parents relationship and peer relationship are all high. In addition, there is a moderate positive and negative correlation between the factors affecting the academic performance of students and their academic performance in Social Studies in terms of teachers’ competency, parents’ occupation, learning environment and peer relationship with Pearson r’s of 0.015,0.403, - 0.069 and -5984. An intervention program was recommended and prepared based on the results of the study.